Circ-PSMB1 knockdown inhibits the pyroptosis of ox-LDL treated human aortic cells via the miR-624-3p/ASC axis - Yupu Zhou; Yongchuan Guo (Journal of Cardiothoracic Surgery)
Abstract Background Atherosclerosis (AS) is a cardiovascular disease that is caused by a variety of factors, including hypertension, diabetes, hyperlipidaemia and smoking. Circular RNAs (circRNAs) have been reported to participate in the progression of AS. Here, we investigated the mechanism by which circ-proteasome 20 S subunit beta 1 (PSMB1) participates in AS. Methods HAECs were stimulated with oxidized low-density lipoprotein (ox-LDL) to establish a model of AS in vitro. Cell viability was investigated with MTT assays. Western blotting and qRT‒PCR were used to measure relative protein and mRNA expression. Cell pyroptosis was analysed by flow cytometry. Lactate dehydrogenase (LDH) levels were measured with a commercial kit. Results We found that circ-PSMB1 and apoptosis-associated speck-like protein containing a CARD (ASC) were overexpressed and miR-624-3p was expressed at low levels in HAECs treated with ox-LDL. Circ-PSMB1 silencing enhanced cell viability and decreased pyroptosis, as shown by the downregulation of IL-1β and IL-18 mRNA expression as well as NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and GasderminD-N (GSDMD-N) protein expression. In addition, the miR-624-3p inhibitor neutralized the effects of si-circ-PSMB1, and ASC overexpression neutralized the effects of the miR-624-3p mimic in ox-LDL-treated HAECs. Conclusion This research demonstrated that circ-PSMB1 might participate in AS development through regulating the pyroptosis of HAECs via the miR-624-3p/ASC axis.